Evaluation of Immunological Parameters in Pregnant Women: Low Levels of B and NK Cells - Juliana Araújo de Carvalho Schettini; Thomás Virgílio Gomes; Claudeir Dias da Silva Júnior; Sandra de Andrade Heráclio; Isabela Cristina Coutinho de Albuquerque Neiva Coelho; Leuridan Cavalcante Torres (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2019)
Abstract Objective To describe the immunological and hematological reference intervals of low-risk pregnant women. Methods A cross-sectional retrospective database analysis of a basic and translational study analyzing the hematological evaluation blood counts and immunophenotyping of TCD3 + , TCD4 + , TCD8 + , B, and natural killer (NK) cells of the peripheral blood in 79 low-risk pregnant women and of 30 control women from the state of Pernambuco, Brazil, was performed. Results No significant differences were detected between the hematological profiles of the 2nd and 3rd trimesters. Nevertheless, the median level of B cells decreased significantly in the 2nd (174 x 103 μL; p < 0.002) and 3rd trimesters (160 x 103 μL; p < 0.001), compared with the control group (296 x 103 μL). Similarly, the median level of NK cells was lower in the 2nd (134 x 103 μL; p < 0.0004) and 3rd trimesters (100 x 103 μL, p < 0.0004), compared with the control group (183 x 103 μL). In contrast, relative TCD4+ and TCD8+ levels increased in the 2nd and 3rd trimesters compared with the controls (TCD4 + : 2nd trimester = 59%; p < 0.001; 3rd trimester = 57%; p < 0.01; control = 50%; and TCD8 + : 2nd trimester = 31%; p < 0.001; 3rd trimester = 36%; p < 0.01; control = 24%). Conclusion Low-risk pregnant women have ~ 40% less B and NK cells in the peripheral blood, compared with non-pregnant women. These parameters may improve health assistance for mothers and contribute to define reference values for normal pregnancies.